Global functional connectivity reveals highly significant differences between the vegetative and the minimally conscious state - Kotchoubey, Boris; Merz, Susanne; Lang, Simone; Markl, Alexandra; Müller, Friedemann; Yu, Tao; Schwarzbauer, Christian (Journal of neurology, 2013)
A major challenge in the diagnosis of disorders of consciousness is the differential diagnosis between the vegetative state (VS) and the minimally conscious state (MCS). Clinically, VS is defined by complete unawareness, whereas MCS is defined by the presence of inconsistent but clearly discernible behavioural signs of consciousness. In healthy individuals, pain cries have been reported to elicit functional activation within the pain matrix of the brain, which may be interpreted as empathic reaction. In this study, pain cries were presented to six VS patients, six MCS patients, and 17 age-matched healthy controls. Conventional task-related functional magnetic resonance imaging (fMRI) showed no significant differences in functional activation between the VS and MCS groups. In contrast to this negative finding, the application of a novel data-driven technique for the analysis of the brain’s global functional connectivity yielded a positive result. The weighted global connectivity (WGC) was significantly greater in the MCS group compared to the VS group (p < 0.05, family-wise error corrected). Using areas of significant WGC differences as ‘seed regions’ in a secondary connectivity analysis revealed extended functional networks in both MCS and healthy groups, whereas no such long-range functional connections were observed in the VS group. These results demonstrate the potential of functional connectivity MRI (fcMRI) as a clinical tool for differential diagnosis in disorders of consciousness.
Published online: 6 November 2012
Gesehen am 04.11.2021